Identification of Houge type of X-linked syndromic mental retardation caused by CNKSR2 truncated variants - Si-Hua Chang; Jie-Yuan Jin; Yi-Qiao Hu; Run-Yan Wang; Rong Xiang; Xia Wang (Italian Journal of Pediatrics)
Abstract Background Houge type of X-linked syndromic mental retardation (MRXSHG) is a type of X-linked condition which is mainly manifested as delayed development, mental retardation, epilepsy that begins at an early age, and delayed language acquisition. MRXSHG is a serious disorder with CNKSR2 variant and at least 34 variants have been identified in MRXSHG patients. However, the genotype-phenotype correlation and variants characteristics of CNKSR2 need further investigation and improvement. Methods Two Chinese MRXSHG families were recruited, and their genetic causes were investigated using whole-exome sequencing (WES), Sanger sequencing, and bioinformatics analysis. To verify the impact of these variants, we used real-time PCR and minigenes consisting of exon 14, intron 14, and exon 15 from both the wild-type and the c.1658-3_1676del DNA sequences. Results In this study, we reported two Chinese boys with MRXSHG and described some rare MRXSHG phenotypes, such as delayed bone age, slightly widened right fissure, and an underdeveloped right temporal lobe, characterized by reduced growth and volume compared to typical development. Two novel variants in CNKSR2 (c.1658-3_1676del and c.1102G > T, p.Gly368*) were identified in these cases. Minigenes results revealed that variant c.1658-3_1676del produced an aberrant spliceosome assembly. Conclusions We identified two novel CNKSR2 variants in MRXSHG families, expanding the variant spectrum of CNKSR2, enriching MRXSHG-related phenotypes, and contributing to genetic counseling for MRXSHG patients.